Modelo de planificación balanceado y modelo de asignación - Oviedo, Jorge; Rubio, Ana (Estudios de Economía, 2016)
Baïou y Balinski (2002) generalized the model of firms-workers allocation toone in which allocation is planned determining both the allocation of workersto firms and how much time workers will dedicate to firms.A planning is stable if there is no pair of firm- worker that could increase theirhours of work together, affecting some less desirable agent.This article studies the relationship between this problem and a matchingproblem, and shows that each stable planning is equivalent to some stablematching.